The Ancient Borobudur Lake, History, and Its Evidences to Develop Geo-archeotourism in Indonesia - Murwanto, Helmy; Purwoarminta, Ananta (Geological Agency, 2019)
DOI: 10.17014/ijog.6.1.103-113In 2015, the number of international tourists who visited Borobudur temple declined and did not reach the government target. It was because there was only one attraction in the temple. After visiting Borobudur, most of tourists move to another place such as Yogyakarta. They know about the temple, but not its past environment when the temple was built. The history and past environment of Borobudur temple could be developed as additional tourist attractions to make them stay longer in that area. Geological condition and the evidences of an ancient lake could be developed as tourist objects. It is very interesting and could be developed to educate visitors in geo-archeology. The aim of this research is to develop archeological (temple) tourism based on geology and past environment. Although many researches on geo-archeology have been done, the results which relate to tourism are still not widely applied yet. The methods used are secondary data analysis and a field survey to investigate the potential of tourist stop sites. The potential tourist attractions were determined by geomorphology, lithology outcrops, stratigraphy, environment, and accessibility. The result is ten stop sites which could be used to describe the paleoenvironment in Borobudur based on geosciences. These tourist objects could explain the environment in the past related to the temple reliefs and ancient human activities.